Single-incision midurethral sling shows less pain and similar success rate in a short-term follow-up compared to the transobturator tape method in the treatment of stress urinary incontinence - Karakeci, Ahmet; Eftal, Taner Cuneyt; Keles, Ahmet; Golbasi, Ceren; Onur, Rahmi (Aves, 2020)
Objective: To compare the efficacy, complications, quality of life, and patient satisfaction rates in women treated for stress urinary incontinence (SUI) using the adjustable anchored single-incision midurethral sling (SIMS) and standard midurethral sling (MUS) procedures. Material and methods: A total of 113 women between October 2012 and October 2016 underwent either the adjustable SIMS (n=54) or MUS (n=57) procedure. The postoperative pain profile was assessed using a 10-point visual analog scale at the fixed time-point quality of life and an additional postoperative 3rd week appointment. We asked our patients the following two questions to evaluate their satisfaction with surgery and their preference: Would you have this kind of surgery again? (Q1), and Would you recommend this type of surgery to another patient with same symptoms? (Q2). For the evaluation of patient complaints, the Incontinence Impact Questionnaire (IIQ-7) and Urinary Distress Inventory (UDI-6) were used before and after the procedure. Results: Women in the SIMS group had a significantly lower postoperative pain profile for up to 3 weeks (p<0.001). There was no significant difference in perioperative complications and postoperative continence rates between the groups. With regard to Q1 and Q2, a significant difference was found between the groups (p=0.003 and p=0.002, respectively). While the questionnaire scores of the IIQ-7 and UDI-6 were also significantly improved at postoperative evaluations (p<0.001), there was no significant difference between the two groups. Conclusion: SIMS is associated with a significantly improved postoperative pain profile and earlier return to work when compared to MUS.
Keywords: Mini-sling; patient satisfaction; single incision